Labor share decline and intellectual property products capital - Dongya Koh; Raül Santaeulàlia-Llopis; Yu Zhen (Queen Mary University of London, School of Economics and Finance, 2018)
We study the behavior of the US labor share over the past 70 years. We find that the capitalization of intellectual property products in the national income and product accounts entirely explains - in a purely accounting sense - the observed decline of the US labor share. We assess the implications of this result for the US macroeconomic model and discuss the way forward.
Keywords: E01; E22; E25; 330; Labor Share; Intellectual Property Products; Capital; 1999- and 2013-BEA Revisions